At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
do you recall how to add and multiply matrixes?
i have subtruct C with B then I lost :S
Adding matrixes is just adding component parts; like vectors right? |4 3| + |1 5 | = |5 8| right? |1 2| |6 6| |7 8|
Is X supposed to be the same for part a and part b? Or are you to find an X matrix for each on ?
just trying to recall my matrix properties; if you want someone elses help; i can always leave :)
its X supposed to be the same for part a and part b
B and C look familiar; like they are .... the same somehow; cant recall how to transform B into C like that.... is it with an inverse matrix?
frankly dont know:S:S
i looked it up; its close; but no; there are different terms in C...bummer
If we subtract B from C we will see what AX has to look like right?
which is prolly what you said you did up there ;)
yeah wich is AX=C-B so we multiply with the inverse of A ?
maybe; what is C-B; can you type it?
C - B = |-2 -4| |-8 -1| right?\[((-2 & -4 \ -8 & -1))\]
the equation editor failed on me lol
AX = |5 3| * |a b| = |5a +3c = -2 5b +3d= -4| |3 2| |c d| |3a +2c = -8 3b +2d= -1| right?
And: |a b| * |5 3| = |5a +b3 = -2 a3 +b2= -4| |c d| |3 2| |c5 +d3 = -8 c3 +d2= -1| if I did it right...
lets see if we can equate these things :) 5a +3c = 5a + 3b 3c - 3b = 0 ---------------- 5b + 3d = 3a + 2b 3b + 3d + 3a = 0 ----------------- 3a + 2c = 5c + 3d 3a -3c - 3d = 0 ----------------- 3b+2d = 3c + 2d 3b - 3c = 0
3b + 3d +3a = 3a -3c -3d 3b + 3c + 6d = 0
my internet source is closing; so thats as far as I can get you :/ good luck with it :) Just equate and solve for a solution to the equations and youll be fine... :)